Pengaruh Manajemen Kelas Terhadap Motivasi Belajar Siswa di MTsN 1 Jombang - Umi Khoiriyah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2018)
Teachers are required to have knowledge and skills enabling them to effectively make a conducive learning environment, design learning procedures, develop good relationships with students and increase attention to the academic activities they manage to motivate students to learn, so that learning objectives are achieved. This study aims to determine whether or not there is an influence between classroom management and student learning motivation. This research method is a quantitative method. In collecting the data, the researcherused questionnaires, then the data analyzed by simple linear regression. The results showed that there is a significant influence between classroom management and student motivation, the results of t countedis greater than t table with 98 degrees of freedom and significance level of 5%, is (19.156>1.66055). The influenceof classroom management toward students’ motivation is 78.9%.